Inhibitory Effect of Salvia miltiorrhiza Extract and Its Active Components on Cervical Intraepithelial Neoplastic Cells - Xuejiao Leng; Hongfei Kan; Qinhang Wu; Cunyu Li; Yunfeng Zheng; Guoping Peng (Molecules, 2022)
The effective treatment of cervical intraepithelial neoplasia (CIN) can prevent cervical cancer. Salvia miltiorrhiza is a medicinal and health-promoting plant. To identify a potential treatment for CIN, the effect of S. miltiorrhiza extract and its active components on immortalized cervical epithelial cells was studied in vitro. The H8 cell was used as a CIN model. We found that S. miltiorrhiza extract effectively inhibited H8 cells through the CCK8 method. An HPLC–MS analysis revealed that S. miltiorrhiza extract contained salvianolic acid H, salvianolic acid A, salvianolic acid B, monomethyl lithospermate, 9‴-methyl lithospermate B, and 9‴-methyl lithospermate B/isomer. Salvianolic acid A had the best inhibitory effect on H8 cells with an IC50 value of 5.74 ± 0.63 μM. We also found that the combination of salvianolic acid A and oxysophoridine had a synergistic inhibitory effect on H8 cells at molar ratios of 4:1, 2:1, 1:1, 1:2, and 1:4, with salvianolic acid A/oxysophoridine = 1:2 having the best synergistic effect. Using Hoechst33342, flow cytometry, and Western blotting analysis, we found that the combination of salvianolic acid A and oxysophoridine can induce programmed apoptosis of H8 cells and block the cell cycle in the G2/M phase, which was correlated with decreased cyclinB1 and CDK1 protein levels. In conclusion, S. miltiorrhiza extract can inhibit the growth of H8 cells, and the combination of salvianolic acid A (its active component) and oxysophoridine has a synergistic inhibitory effect on H8 cells and may be a potential treatment for cervical intraepithelial neoplasia.